Physico-chemical and rheological characterisation of sweet potato flours and dough - Mohd Hanim, Abu Bakr (2014)
Physico-chemical and rheological characterisation of a new variety of sweet potato flour and dough, the VitAto, known for its high vitamin A contents, were compared with two other commercial sweet potato, the Bukit Naga and Okinawan available in Malaysia. The recoveries of each sweet potato from milling were not significantly different at about 20% but in proximate analysis, the VitAto presented the highest protein, 5.7% and dietary fiber, 14.8% contents with more energy 399.6 kcal/100g produced. The VitAto flour has average particle size of 132.04 μm. The pasting temperature of the VitAto flour was 65°C, with highest setback and trough viscosity values of 530.90 and 197.20 mPa.s, respectively. The flour is classified as easy flowing and stable powders. The rheological properties of sweet potato doughs at different mixing time were studied. In the large deformation extension test,extensibility parameters including dough length at fracture, measured and actual forces acting on dough strips were obtained for calculating the stress-strain data. For the small deformation test, both modulus of elasticity and viscosity (G) were studi The extensibility of dough from sweet potato flour increased to its peak at 5 minutes mixing time before decreasing illustrating an optimum mixing time. The variety of VitAto which had a higher protein content of 5.7% has higher values of all the extensibility parameters when compared with the other varieties of sweet potato flours, Bukit Naga and Okinawan. The flow behavior index, n of sweet potato dough which were between 1.82 to 2.11 indicated that they were also of strain hardening nature similar to the wheat doughs but at a lower magnitude suggesting suitability in a wide range of application for the snack or confectionary industries. The small deformation tests were not able to identify the optimum mixing time although in general illustrated that sweet potato dough was essentially elastic or recoverable. The Pearson correlations of large and small deformation tests showed that the rheological parameters were positively correlated among themselves in the evaluation of the effect of mixing time to rheological properties of sweet potato dough.